Search for chargino and neutralino production in final states with a Higgs boson and missing transverse momentum at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (Physical review, 2019)
A search is conducted for the electroweak pair production of a chargino and a neutralino pp -> (chi) over tilde (+/-)(1)(chi) over tilde (0)(2), where the chargino decays into the lightest neutralino and a W boson, (chi) over tilde (+/-)(1) -> (chi) over tilde W-0(1)+/- while the neutralino decays into the lightest neutralino and a Standard Model-like 125 GeV Higgs boson,(chi) over tilde (0)(2) -> (chi) over tilde (0)(1)h. Fully hadronic, semileptonic, diphoton, and multilepton (electrons, muons) final. states with missing transverse momentum are considered in this search. Higgs bosons in the final state are identified by either two jets originating from bottom quarks (h -> b (b) over bar), two photons (h -> gamma gamma), or leptons from the decay modes h -> WW, h -> ZZ or h -> tau tau. The analysis is based on 36.1 fb(-1) of s root s = 13 TeV proton-proton collision data recorded by the ATLAS detector at the Large Hadron Collider. Observations are consistent with the Standard Model expectations, and 95% confidence-level limits of up to 680 GeV in (chi) over tilde (+/-)(1)/(chi) over tilde (0)(2) mass are set in the context of a simplified supersymmetric model.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration: C. Anders, V. Andrei, C. Antel, A.E. Baas, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, L. Helary, J. Jongmanns, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schöning, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 05.09.2019